Modern Digital and Technological Educational Methods - Angelos I. Stoumpos; Rodanthi I. Stoumpou (Trends in Higher Education, 2025)
The development and evolution of digital technologies can contribute to the transformation of the educational sector, allowing the integration of innovative teaching approaches. Typical examples of such approaches include artificial intelligence, augmented and virtual reality (AR/VR), adaptive learning, and online educational environments. This study explores modern digital educational methods, focusing on the advantages, challenges, and future prospects of modern technologies in education. The systematic literature review was based exclusively on the Scopus database. We explored 948 articles published from 1968 to 2025. Furthermore, using the VOSviewer program (version 1.6.20), the results were analyzed, identifying and highlighting various trends and key thematic areas. However, although digital educational methods are able to provide greater interactivity, personalization, and flexibility in learning, they also face significant challenges, some of which are the digital divide, privacy protection, and teacher training. In the future, research should shape best practices that will integrate digital technologies into education.